Rosario+Vampire. 09, Monster mamas - Ikeda, Akihisa, 1976- (VIZ Media, 2009)
The academy's headmaster restores Tsukune's humanity by chaining a "spirit lock" to his wrist then pressures him into joining the school's Festival Committee, where Tsukune meets charismatic Hokuto. Hokuto chaims he wants to bring peace to the school. Unfortunately, his method is to destroy the Great Barrier that separates Yokai from the human world...!